Calcium‐sensing receptor (CaSR) as a novel target for ischemic neuroprotection. (3rd October 2014) - Kim, Jong Youl; Ho, Hanson; Kim, Nuri; Liu, Jialing; Tu, Chia‐Ling; Yenari, Midori A.; Chang, Wenhan
Abstract Object Ischemic brain injury is the leading cause for death and long‐term disability in patients who suffer cardiac arrest and embolic stroke. Excitotoxicity and subsequent Ca2+‐overload lead to ischemic neuron death. We explore a novel mechanism concerning the role of the excitatory extracellular calcium‐sensing receptor (CaSR) in the induction of ischemic brain injury. Method Mice were exposed to forebrain ischemia and the actions of CaSR were determined after its genes were ablated specifically in hippocampal neurons or its activities were inhibited pharmacologically. Since the CaSR forms a heteromeric complex with the inhibitory type B γ‐aminobutyric acid receptor 1 (GABABR1), we compared neuronal responses to ischemia in mice deficient in CaSR, GABABR1, or both, and in mice injected locally or systemically with a specific CaSR antagonist (or calcilytic) in the presence or absence of a GABABR1 agonist (baclofen). Results Both global and focal brain ischemia led to CaSR overexpression and GABABR1 downregulation in injured neurons. Genetic ablation of Casr genes or blocking CaSR activities by calcilytics rendered robust neuroprotection and preserved learning and memory functions in ischemic mice, partly by restoring GABABR1 expression. Concurrent ablation of Gabbr1 gene blocked the neuroprotection caused by the Casr gene knockout. Coinjection of calcilytics with baclofen synergistically enhanced neuroprotection. This combined therapy remained robust when given 6 h after ischemia. Interpretation Our study demonstrates a novel receptor interaction, which contributes to ischemic neuron death through CaSR upregulation and GABABR1 downregulation, and feasibility of neuroprotection by concurrently targeting these two receptors.